Compulsory Arbitration in British Columbia : Bill 33 - Tsong, Peter (Relations industrielles / Industrial Relations, 1971)
The author presents the reasons for the introduction of Bill 33 in British Columbia, examines the disputes which were settled under it, evaluates its impact on the frequency and the duration of work stoppages, and its role in the future of labour management relations in this province.